Country Differences in the Effects of Individual Traits on Depression in Women in Europe - Rodríguez-Donate, M. Carolina; Nieto-González, Imanol L.; Guirao-Pérez, Ginés (International journal of mental health and addiction, 2025)
Mental health and, in particular, depression are of great global concern today, especially in middle- and high-income countries. These health issues show an unequal gender prevalence as they are more common in women than in men. The aim of this work is to use micro-econometric models to analyze the prevalence of depression in women in 27 European countries, as well as to quantify the effects of certain individual characteristics on the probability of experiencing depression and the degree to which it occurs. In addition, measures are proposed to assess how each country differs from the total sample. The data used proceed from the European Health Interview Survey wave 2 (EHIS-2). The results show that higher educational levels and incomes are protective factors, while older age and being unemployed have a positive effect on the probability of having depression, particularly on the probability of severe depression. Furthermore, from the calculation of ratios, notable differences are detected in the effects of these characteristics in different countries. Although the direction of the effect of each characteristic is similar in all countries, the size of the effect in each country varies significantly from the sample average. The results highlight the importance of identifying which individual traits generate a higher propensity to experience depression in women. The proposed procedure leads to the conclusion that the detection of differences and similarities between countries could allow the extrapolation of successful practices in prevention and mental health care.